Effects of slackline training on postural control, jump performance, and myoelectrical activity in female basketball players - Santos, L.; Fernández-Rio, J.; Fernández-Garcia, B.; Jakobsen, M. D.; González-Gómez, L.; Suman, O. E. (The Journal of Strength and Conditioning Research, 2016)
The main goal of the study was to assess the effects of slackline training on the postural control system and jump performance of athletes. Twenty-five female basketball players were randomized into 2 groups: control (N = 12) and experimental (N = 13). The latter experienced a 6-week supervised slackline training (3 sessions per week, 5-9 minutes per session). Participants underwent center of pressure (CoP) testing through three 10-second tasks (bipedal, left leg, and right leg support) over firm and compliant surfaces with eyes open. Several CoP parameters were assessed: length, area, length/area, speed, Ymean, Xmean, deltaY, deltaX, RMS (root-mean-squared amplitude of the CoP), RMSY, and RMSX. Surface electromyography recordings were obtained too. Participants were also tested on jump performance, provided perceived exertion (6-20 Borg scale) and local muscle perceived exertion. Center of pressure parameters significantly differed before and after training only in the experimental group and only on the compliant surface (left leg: length, area, speed, deltaY, and deltaX; right leg: length, speed, Ymean, deltaY, and RMSY). Surface electromyography recordings were comparable before and after training in both groups. Performance on a countermovement jump test significantly improved only in the experimental group (effect side was 3.21 and 1.36 [flight time and jump height, respectively], which is described as a large effect). Mechanical power of the legs, as measured through the 30-second maximal performance jump test, did not improve in either group. The slackline training was rated as "somewhat hard" with the quadriceps, soleus, and gastrocnemius being rated as the most engaged muscles. Data indicate that slacklining requires activation of the main lower limb muscles. On conclusion, slacklining may be a valid cross-training tool for female basketball players.